Zoogeography of the echiuran fauna of the East Pacific Ocean (Phylum: Echiura) - Biseswar, Ramlall (Zootaxa, 2012)
This report provides a checklist of the echiuran fauna of the East Pacific Ocean and analyses their distribution. All thespecies are mapped and keys for their identification are provided. Currently the echiuran fauna of the East Pacificcomprises three families, 9 genera and 17 species. The family Bonelliidae contains two genera and three species, theUrechidae has a single genus with two species, and the Echiuridae contains six genera and 12 species. This investigationshows that the East Pacific has a very low species diversity comprising only about 10% of the world fauna. Of the recordedspecies in the East Pacific, 12 are found in the North Pacific, four are circumtropical and only two species are found in theSouth Pacific. Ochetostoma baronii is the only species considered to be cosmopolitan and eleven species appear to be endemic to the Eastern Pacific.